Statistical analysis for the social sciences - Kurtz, Norman R. (Boston : Allyn and Bacon, 1999)
This book is about: Social statistics and measurement; Displaying data; Numerical summaries of data; A continuous probability distribution; ...
Keywords: Social sciences; Statistical methods; Social sciences -- Statistical methods